PENGELOLAAN BERBASIS PARTISIPATIF UNTUK PENINGKATAN NILAI EKOLOGIS HUTAN MANGROVE DI PULAU SABANGKO - Rahmawati Nurkarima; Alfiani Dwi Astuti; Fitriyani Saudi; Nurhasanah (Jurnal Celebica : Jurnal Kehutanan Indonesia, 2025)
A study has been conducted on community participation in mangrove management on Sabangko Island. The aim was to determine the forms of community participation related to mangrove management on Sabangko Island. In addition, this study sought to determine the ecological value of mangrove forests on Sabangko Island. This study used a descriptive qualitative research type. Data collection used direct observation and questionnaires. Then, the data was combined with the results of interviews. This study used 68 families as samples in the data collection process. From the results of the study, it can be concluded that the community is very aware of the ecological benefits of the mangrove ecosystem. The form of local community participation is mostly abstract participation. The ecological value of mangroves most perceived by the local community is maintaining the availability of fresh water on the island